Analysis of trust factors, brand image, and promotions influencing customer loyalty to GoFood services in Solo Raya - Zahroh Febriani Saputri; Putri Maisara (Universitas Pendidikan Nasional, 2023)
This study employed a quantitative research approach, with data collection conducted through a questionnaire distributed to respondents. The sample size comprised 140 individuals residing in Solo Raya who were regular users of GoFood services. Sampling was conducted using non-probability sampling, specifically purposive sampling. The research aimed to assess customer loyalty to GoFood, given the proliferation of advanced brands in online transportation services, particularly the Online Food Delivery (OFD) feature. The study examined several factors influencing customer loyalty, including trust, brand image, and promotion, as independent variables. In conclusion, the findings indicated that trust and brand image had a positive and significant impact on customer loyalty, while promotion had a positive but non-significant influence. Thus, all independent variables played a crucial role in shaping customer loyalty towards GoFood services, although promotion did not significantly impact GoFood customer loyalty.